A recent advancement on the applications of nanomaterials in electrochemical sensors and biosensors. (December 2022) - Ramya, M.; Senthil Kumar, P.; Rangasamy, Gayathri; Uma shankar, V.; Rajesh, G.; Nirmala, K.; Saravanan, A.; Krishnapandi, Alagumalai
Abstract: Industrialization and globalization, both on an international and local scale, have caused large quantities of toxic chemicals to be released into the environment. Thus, developing an environmental pollutant sensor platform that is sensitive, reliable, and cost-effective is extremely important. In current years, considerable progress has been made in the expansion of electrochemical sensors and biosensors to monitor the environment using nanomaterials. A large number of emerging biomarkers are currently in existence in the biological fluids, clinical, pharmaceutical and bionanomaterial-based electrochemical biosensor platforms have drawn much attention. Electrochemical systems have been used to detect biomarkers rapidly, sensitively, and selectively using biomaterials such as biopolymers, nucleic acids, proteins etc. In this current review, several recent trends have been identified in the growth of electrochemical sensor platforms using nanotechnology such as carbon nanomaterials, metal oxide nanomaterials, metal nanoparticles, biomaterials and polymers. The integration strategies, applications, specific properties and future projections of nanostructured materials for emerging progressive sensor platforms are also observed. The objective of this review is to provide a comprehensive overview of nanoparticles in the field of electrochemical sensors and biosensors. Graphical abstract: Image 1 Highlights: A summary of the various nanomaterials used for electrochemical and biosensors was presented. In order to evaluate the characteristic performance of sensors, a performance analysis was discussed. Sensors and biosensors based on advanced electrochemical technology. An investigation is conducted into the importance of nanomaterials and their behavioral properties. A sensor technology that is used to monitor the health of humans and the environment.